Inclusion of Students with Disabilities in a Socio-Cultural Perspective: What is the Perception of Physical Educatio Teachers? - Sari, Merlina; Risma, Nova; Gazali, Novri; Rodia, Nurafni (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
This study aims to examine teachers' perceptions of inclusive physical education in Pekanbaru City and the identity of the factors that influence their perceptions from a socio-cultural perspective. This research is qualitative. The research subjects recruited were physical education teachers in Pekanbaru City. The selection of participants is based on two criteria: (i) teachers who have earned a Bachelor's degree in Physical Education and (ii) teachers who teach students with disabilities in public and private junior high schools. Based on these criteria, only five physical education teachers were found. Individual interviews were conducted with each teacher. Deductive and inductive analysis processes are used to organize and report the data. The results showed that teachers believed general physical education classes were a good place to develop students with disabilities. Teachers realize that students with disabilities can have equal opportunities to participate in general physical education programs and develop social skills. Although the teachers recognized these benefits, they also expressed concern about the instructional and environmental barriers to the inclusion of students with disabilities in mainstream sports programs. Future research should address the importance of teachers' beliefs and practices about effective teaching in inclusive.